PENERAPAN MODEL PEMBELAJARAN KOOPERATIF ACCELERATED LEARNING UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DI KELAS XI IPA SMA NEGERI 6 PEKANBARU - Erni Eskarina Erni Eskarina; Miharty ' '; Armiyus Thaib Armiyus Thaib (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The objective of this research is to improve student’s achievement is comprehend Hidrocarbon topic of the second year students at SMAN 6 Pekanbaru. The writer carried out experimental research was focus by using Randomized Control Group Pretest-Postest. The research was implemented at SMAN 6 Pekanbaru. The sample of this research were XI IPA 2 as an experimental class and XI IPA 3 as a control class. The experimental class applied Discovery Learning method with using Cooperative Accelerated Learning Model. Meanwhile control class applied Discovery Learning method without using Cooperative Accelerated Learning model. The tada analysis technique was test t. Based on the result of data analysis showed that t observed > t table with score 2,7546 > 1,67, it means that implementation of Cooperative Accelerated Learning Model able to improve student’s achievement in comprehend hidrocarbon topic at XI IPA SMAN 6 Pekanbaru with 11,06% of coefficient effect.Keywords : Accelerated Learning, Learning Achievement, and Hidrocarbon